2021
DOI: 10.21037/gs-21-620
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of malignant sublingual gland tumors: a narrative review

Abstract: Objective: In this article we review the literature on the malignant sublingual gland tumors from a surgical perspective.Background: Sublingual gland tumors occur with a very low incidence and most are malignant tumors.The extent of treatment, clinical outcomes and prognosis of malignant sublingual gland tumors have not been well defined, due to the rarity of this disease.Methods: A database search using Web of Science (https://webofknowledge.com/) and PubMed (https:// pubmed.ncbi.nlm.nih.gov/) was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…In the current study, the 5‐year OS and DFS of the 79 patients with MSLGT was 85.7% and 71.7%, respectively, while that in other retrospective studies of MSLGT ranged from 69% to 77.7%. (Kojima et al, 2020; Lee et al, 2016; Liu et al, 2017; Park, Cho, et al, 2021). Lee et al (2016) analyzed the surveillance, epidemiology, and end results (SEER) database and found that the 5‐year OS for 210 patients was 69%, which is lower than our estimation (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the 5‐year OS and DFS of the 79 patients with MSLGT was 85.7% and 71.7%, respectively, while that in other retrospective studies of MSLGT ranged from 69% to 77.7%. (Kojima et al, 2020; Lee et al, 2016; Liu et al, 2017; Park, Cho, et al, 2021). Lee et al (2016) analyzed the surveillance, epidemiology, and end results (SEER) database and found that the 5‐year OS for 210 patients was 69%, which is lower than our estimation (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…MSLGT has some potential for cervical nodal metastasis and distant metastasis, and some patients may suffer from local and regional recurrence. A few of patients with MSLGT pathological types are at some risk of cervical nodal metastasis, with a documented metastasis rate of up to 60% for non‐ACC malignant sublingual gland tumors (Park, Cho, et al, 2021). However, ACC is more frequent among sublingual gland malignancies therefore, cervical nodal metastasis of MSLGT is not that common when compared with other major salivary gland malignancies (Liu, Lu, et al, 2022; Lombardi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, the preservation of the ductal system must be considered; otherwise, excision of the ipsilateral submandibular gland is recommended. 33 For large tumors, en bloc resection is the common first option. Additionally, lingual nerve ablation is usually required to achieve a negative margin.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutics for salivary glands remain a poor option; the last clinical trial looking into doxorubicin to treat advanced carcinoma was conducted in 1996 and reported a meager 27% response rate ( 190 ). More recent studies looking at antibody therapies have been equally disappointing; although anti-EGFR and anti-HER2 therapies make some improvement, many patients ultimately develop resistance and do not reach remission ( 191 , 192 ). Though other therapeutics are under investigation, a better understanding of critical genes that can drive a terminally differentiated salivary gland duct or acinar cell back to a stem-like state would likely facilitate the development of more effective therapeutics ( 193 ).…”
Section: Discussionmentioning
confidence: 99%